2023
DOI: 10.3389/fphar.2023.1211675
|View full text |Cite
|
Sign up to set email alerts
|

Role of anoikis-related gene PLK1 in kidney renal papillary cell carcinoma: a bioinformatics analysis and preliminary verification on promoting proliferation and migration

Abstract: Background: Kidney renal papillary cell carcinoma (KIRP) is a rare malignancy with a very poor prognosis. Anoikis is a specific form of apoptosis involved in carcinogenesis, but the role of anoikis in KIRP has not been explored.Methods: Anoikis-related genes (ARGs) were obtained from the GeneCards database and Harmonizome database and were used to identify different subtypes of KIRP and construct a prognostic model of KIRP. In addition, we also explored the immune microenvironment and enrichment pathways among… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…In addition, they delved deeper into the functional significance of Plk1 in KIRP and uncovered that silencing Plk1 in KIRP significantly curtailed cell proliferation, clonogenicity, and migratory capacity. 55 Thus, this creates newer avenues for research in generating potential drugs for RCC along with other grave tumor-related kidney disorders in the near future.…”
Section: Plk1 In Ktsmentioning
confidence: 99%
“…In addition, they delved deeper into the functional significance of Plk1 in KIRP and uncovered that silencing Plk1 in KIRP significantly curtailed cell proliferation, clonogenicity, and migratory capacity. 55 Thus, this creates newer avenues for research in generating potential drugs for RCC along with other grave tumor-related kidney disorders in the near future.…”
Section: Plk1 In Ktsmentioning
confidence: 99%
“…Recent studies have shown that anoikis has potential therapeutic value in RCC. Some anoikis key genes was reported to promote proliferation and migration in RCC [ 6 ]. In addition, progression of RCC can be inhibited by reversing anoikis resistance [ 7 ].…”
Section: Introductionmentioning
confidence: 99%